Sources of hepatic glycogen synthesis following a milk-containing breakfast meal in healthy subjects - Barosa, Cristina; Silva, Claudia; Fagulha, Ana; Barros, Luísa; Caldeira, M. Madalena; Carvalheiro, Manuela; Jones, John G. (Metabolism, clinical and experimental, 2012)
During feeding, dietary galactose is a potential source of hepatic glycogen synthesis; but its contribution has not been measured to date. In the presence of deuterated water ( 2H 2O), uridine diphosphate (UDP)–glucose derived from galactose is not enriched, whereas the remainder derived from glucose-6-phosphate (G6P) is enriched in position 2 to the same level as body water, assuming complete G6P–fructose-6-phosphate (F6P) exchange. Hence, the difference between UDP-glucose position 2 and body water enrichments reflects the contribution of galactose to glycogen synthesis relative to all other sources. In study 1, G6P-F6P exchange in 6 healthy subjects was quantified by supplementing a milk-containing breakfast meal with 10 g of [U- 2H 7]glucose and quantifying the depletion of position 2 enrichment in urinary menthol glucuronide. In study 2, another 6 subjects ingested 2H 2O and acetaminophen followed by an identical breakfast meal with 10 g of [1- 13C]glucose to resolve direct/indirect pathways and galactose contributions to glycogen synthesis. Metabolite enrichments were determined by 2H and 13C nuclear magnetic resonance. In study 1, G6P-F6P exchange approached completion; therefore, the difference between position 2 and body water enrichments in study 2 (0.20% ± 0.03% vs 0.27% ± 0.03%, P < .005) was attributed to galactose glycogenesis. Dietary galactose contributed 19% ± 3% to glycogen synthesis. Of the remainder, 58% ± 5% was derived from the direct pathway and 22% ± 4% via the indirect pathway. The contribution of galactose to hepatic glycogen synthesis was resolved from that of direct and indirect pathways using a combination of 2H 2O and [1- 13C]glucose tracers.